Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1063/1.1482150
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency near-field microscopy

Abstract: Conventional optics in the radio frequency ͑rf͒ through far-infrared ͑FIR͒ regime cannot resolve microscopic features since resolution in the far field is limited by wavelength. With the advent of near-field microscopy, rf and FIR microscopy have gained more attention because of their many applications including material characterization and integrated circuit testing. We provide a brief historical review of how near-field microscopy has developed, including a review of visible and infrared near-field microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
133
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(140 citation statements)
references
References 272 publications
0
133
0
3
Order By: Relevance
“…Three distinct structural phases, as seen from the high resolution TEM images and the selected-area electron diffraction (SAED) patterns in Fig. 3a, are observed in ribbons in the [11][12][13][14][15][16][17][18][19][20] growth direction. Correspondingly, typical I-V characteristics of the three phases are shown in Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Three distinct structural phases, as seen from the high resolution TEM images and the selected-area electron diffraction (SAED) patterns in Fig. 3a, are observed in ribbons in the [11][12][13][14][15][16][17][18][19][20] growth direction. Correspondingly, typical I-V characteristics of the three phases are shown in Fig.…”
mentioning
confidence: 99%
“…3b. It has been previously reported that pristine VLS-grown [11][12][13][14][15][16][17][18][19][20] In 2 Se 3 nanoribbons with superlattice structures (Fig. 3a, left) exhibit metallic behavior and room temperature R 2T as low as kilo-ohms 10 .…”
mentioning
confidence: 99%
“…Apertureless probes are commonly represented by open-ended coaxial structures. These probes generate very tight near field pattern with full-width at half-maximum (FWHM) less that λ/10 at around λ/50-λ/100 standoff distance however electromagnetic coupling of these probes to the sampled material is extremely weak, considerably limiting the image resolution amplitude contrast to less than 1-2dB [8]. The other class of probes is represented by the openended waveguide structures or apertures in conductive screens [1], [10]- [13].…”
Section: Introductionmentioning
confidence: 99%
“…The essential part of any reflectometry system responsible for electromagnetic (EM) interaction with the sample and reflected signal collection is a sensing probe. This can be apertureless [8], [9] or aperture-based [1], [8], [10]. Apertureless probes are commonly represented by open-ended coaxial structures.…”
Section: Introductionmentioning
confidence: 99%
“…Coaxial AFM probes have previously been used for microassembly 11 and near field optical and microwave microscopy. 12 In this paper, we demonstrate dielectrophoretic imaging with a coaxial AFM probe. Imaging with dielectrophoresis ͑DEP͒ can provide topographical information as well as information about the local dielectric constant and spectrum.…”
mentioning
confidence: 99%